Description of Anoplophora fanjingensis sp. n. (Coleoptera, Cerambycidae, Lamiinae) from southwest China - Yang, Shulin (Biodivers Data J, 2020)
BACKGROUND: Anoplophora Hope, 1839 is a genus including more than 40 species occurring in Asia. Most species of this genus have beautiful colours on the elytra and are of great interest to insect collectors. Due to their developing in and consuming wood in the larval stage, species in this genus could be economically important, such as A. glabripennis, an introduced species to North America. NEW INFORMATION: We described Anoplophora fanjingensis sp. n., based on specimens from Mount Fanjing (also Fanjingshan), Jiankou County, Guizhou, China. The new species is characterised by its elytra with metallic iridescent sheen and the non-annulated antennae. Habitus of two similar species, Anoplophora chiangi and Anoplophora leechi, are also presented.